2021
DOI: 10.3389/fvets.2021.673809
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Usage Pattern in Broiler Chicken Flocks in Germany

Abstract: In this work, antimicrobial usage data from 2,546 commercial broiler chicken flocks originating from 37 farms are presented. Antimicrobial usage data at the flock level were based on mandatory documentation of antibiotic treatments in livestock in Germany, collected retrospectively for the time period of 2013–2018. The data encompasses all antimicrobial treatments during the fattening period of each flock, starting with the placement of day-old chicks at the barn. The aim of this analysis was to investigate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…Remarkably, colistin is only listed as highly, and not critically, important for animals in general [ 29 ], and many countries around the world use only small amounts of colistin to treat animals or have prohibited its use. This is in contrast with Germany, where it is regularly administered in veterinary medicine and where various authors have described a lack of alternatives for certain infectious diseases in animals [ 14 , 64 , 73 ]. Until recently, only veterinarians used colistin due to its toxicity in humans, making it a more appropriate choice for usage in veterinary medicine than cephalosporins and fluoroquinolones.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Remarkably, colistin is only listed as highly, and not critically, important for animals in general [ 29 ], and many countries around the world use only small amounts of colistin to treat animals or have prohibited its use. This is in contrast with Germany, where it is regularly administered in veterinary medicine and where various authors have described a lack of alternatives for certain infectious diseases in animals [ 14 , 64 , 73 ]. Until recently, only veterinarians used colistin due to its toxicity in humans, making it a more appropriate choice for usage in veterinary medicine than cephalosporins and fluoroquinolones.…”
Section: Discussionmentioning
confidence: 98%
“…In 2013, the project continued as a longitudinal approach. For this, data collection occurred semi-annually via veterinarians or farmers, using an open cohort with ongoing recruitment, to balance out possible withdrawals [ 73 , 90 , 91 ].…”
Section: Methodsmentioning
confidence: 99%
“…More than half of the poultry practitioners (n = 133/250, 53.2%) indicated very low to low metaphylaxis use, which is in sharp contrast to current market practices: Firstly, poultry is almost exclusively held in larger flocks and any disease diagnosed in poultry flocks requires treatment of the whole group irrespective of the morbidity rate and therefore inevitably treating a proportion of animals which are not (yet) showing clinical signs, reflecting the legal definition of metaphylaxis [ 6 , 8 , 10 ]. Secondly, VMPs for poultry are almost exclusively available as oral formulations and exclude therefore individual treatment [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though all major farmed animals are gregarious, weaning represents a major stressor and subsequent (intra- or inter-farm) transport followed by regrouping adds to this, especially for calves. Some studies demonstrated that metaphylaxis in commercially reared cattle and pig holdings was most often implemented after weaning, transportation, and co-mingling, as these periods of stress are often followed by disease [ 6 , 7 , 8 ]. The antibiotic sales data mirror these findings as they represent a surrogate measure for animal group medications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, issues on the comparability of exposure of animal populations have been raised using the concept of defined daily doses in the veterinary field. On account of the massive growth of young meat producing animals such as broiler chicks, a variation in time of treatment may lead to substantial over or underestimation of the number of animals actually treated [ 55 ]. It has therefore been recommended to also collect data on the number of animals treated and the dosage [ 20 ].…”
Section: Discussionmentioning
confidence: 99%